Digital innovations in delivering social protection in rural areas: Lessons for public provisioning during the post-pandemic recovery and beyond - Beatriz Burattini; Gabriela Perin; Krista Alvarenga; Varsha Valiyaparambil (International Policy Centre for Inclusive Growth (IPC-IG), 2022)
Over the past 20 years, considerable progress has been made in reducing poverty worldwide, with the expansion of social protection coverage and uptake playing a key role. To strengthen and expand the public provision of social protection, countries have been investing in the development of robust delivery systems, including digital tools, especially identification and payment systems and social registries. This report discusses the potential of digital technology to improve social protection performance in rural areas, as well as its limitations.
Keywords: 330; social protection; digitalisation; rural poverty